2022
DOI: 10.3390/molecules27030582
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and DFT Studies of a Novel Set of Spiropyrrolidines Tethered with Thiochroman-4-one/Chroman-4-one Scaffolds

Abstract: A novel series of 14 spiropyrrolidines bearing thiochroman-4-one/chroman-4-one, and oxindole/acenaphthylene-1,2-dione moieties were synthesized and characterized by spectroscopic techniques, as well as by three X-ray diffraction studies, corroborating the stereochemistry. Quantum chemical calculations studies, using the DFT approach, were performed to rationalize the stereochemical outcome. These N-heterocycles were evaluated for their antibacterial and antifungal activities against some pathogenic organisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 81 publications
0
29
0
Order By: Relevance
“…The electrophilicity (ω) of the molecules describes their tendency to attract electrons. As a result, the enhanced bioactivity of ( 11 a – j ) may be explained by their ability to donate electrons to the biological target, which may be important for active site stabilization [52] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrophilicity (ω) of the molecules describes their tendency to attract electrons. As a result, the enhanced bioactivity of ( 11 a – j ) may be explained by their ability to donate electrons to the biological target, which may be important for active site stabilization [52] …”
Section: Resultsmentioning
confidence: 99%
“…As a result, the enhanced bioactivity of (11 a-j) may be explained by their ability to donate electrons to the biological target, which may be important for active site stabilization. [52] Furthermore, the various substituents in molecules (3, 11 aj) play an important role in determining their molecular descriptors e. g., ionization energies (IP), electron affinities (EA), chemical hardness (η) and softness (S) which impacts their efficacy. These molecular descriptors are thoroughly examined in order to clarify the structure-activity relationships of the molecules under consideration.…”
Section: Chemistryselectmentioning
confidence: 99%
“…Chroman‐4‐one is very similar in structure to naphthalene‐1,4‐dione. Also chroman‐4‐one is the pharmacophore of some antimicrobial compounds [20,21] . We hypothesized that it is possible to synthesize derivatives with anti‐mycobacterial activity based on the chroman‐4‐one scaffold.…”
Section: Resultsmentioning
confidence: 99%
“…[91] Very recently Chouchene et al (2022) reported series of similar spiro-chromano-pyrrolidines via diastereoselective 1,3dipolar cycloaddition of in-situ generated azomethine ylide and (E)-3-arylidene-4-chromanones 1 & (E)-3-arylidene-thiochromanones 2 in good yields. [92] Refluxing a solution of (E)-3arylidene-4-chromanones 1 or (E)-3-arylidene-thiochromanones 2, glycine ethyl ester and indoline-2,3-dione (isatin) 83 or acenaphthenequinone 84 in CH 3 CN, in presence of triethylamine afforded corresponding spiropyrrolidine-chromanone ). [93] The synthesis involves the reaction of N-(4-chlorobenzylidene)-glycine methyl ester 89 with (E)-3-arylidene-4-chromanones 1 in presence of catalytic amount of Cu(I)/TF-bipham-phos 90 and Et 3 N to afford the pure single cycloadduct spiro-(chromane-3,3'-pyrrolidine)-4one 91 (ee:89-94% & dr: > 98%) possessing four adjacent stereo-genic centers including the spiro-centre (Scheme 32).…”
Section: Spiro[chromane-33'-pyrrolidin]-4-onesmentioning
confidence: 99%
“…Very recently Chouchene et al . (2022) reported series of similar spiro ‐chromano‐pyrrolidines via diastereoselective 1,3‐dipolar cycloaddition of in‐situ generated azomethine ylide and ( E )‐3‐arylidene‐4‐chromanones 1 & ( E )‐3‐arylidene‐thiochromanones 2 in good yields [92] . Refluxing a solution of ( E )‐3‐arylidene‐4‐chromanones 1 or ( E )‐3‐arylidene‐thiochromanones 2 , glycine ethyl ester and indoline‐2,3‐dione (isatin) 83 or acenaphthenequinone 84 in CH 3 CN, in presence of triethylamine afforded corresponding spiropyrrolidine‐chromanone 85 / 87 thiochromane 86 / 88 hybrids as a single diastereomer in good yields (Scheme 31).…”
Section: Spiro‐chromano‐based Heterocyclesmentioning
confidence: 99%